Effects of rotational speed on microstructure, exothermic reactions and mechanical properties of Al/Ni energetic structural materials prepared by hot pressing and friction stir processing - Mingzhi Wang; Hongchen Liu; Sainan Gu; Yun Wu; Ziqi Wei; Jian Wang; Li Xie; Yalin Lu; Jiangtao Wang (Journal of Materials Research and Technology, 2024)
In order to fabricate Al/Ni energetic structural materials (ESMs) with high energy density and mechanical properties, a novel approach of hot pressing and friction stir processing (HP-FSP) was employed in this study. The effects of rotational speed on microstructure, exothermic reactions and mechanical properties of Al/Ni ESMs were investigated. The microstructure characteristics were characterized via scanning electron microscopy, transmission electron microscopy and X-ray diffraction. Differential scanning calorimeter, quasi-static compression and microhardness tests were conducted to analyze the energy density and mechanical properties, respectively. The results showed that the compressive strength and the energy density of Al/Ni ESMs without friction stir processing (FSP) were 183 MPa and 1110 J/g, respectively. Numerous Ni particles were broken and elongated to irregular granules and fibrous microstructure during FSP procedure. As the rotational speed reached 800 rpm, the Al/Ni ESMs prepared by HP-FSP method exhibited excellent comprehensive properties with the compressive strength of 416 MPa and the energy density of 856 J/g. With the increasing rotational speed, the compressive strength, elastic modulus and maximum microhardness increased first and then decreased, and the energy density decreased gradually. It was found that the enhancement of mechanical strength was attributed to dislocation strengthening and second phase strengthening. The reduction of exothermic energy density was ascribed to the increasing heat input of FSP treatment, intensifying the reaction diffusion in Al/Ni interfaces and promoting the generation and proliferation of Al3Ni phases.